Factors Causing the Withdrawal of Foreign Retailers from the Korean Retail Market - 조경출 (한국농촌경제연구원, 2007)
Most experts agree that Wal-Mart and Carrefour are a few of the largest retailers in the world. Wal-Mart and Carrefour have been doing their businesses well domestically and globally. But, after experiencing hardships, Wal-Mart and Carrefour evacuated their business units from Korea in 2006. Wal-Mart and Carrefour, the largest and second-largest retailers, failed in the Korean retail market, which is one of the fast-rising emerging markets in Asia. The failure of these two retailers in Korea attracts many researchers and C.E.O.s in the retail business as the failure represents an empirical showing that success in a home country does not guarantee success internationally. However, the literature focused on this issue is scarce. This paper investigated the factors that have caused the failure of Wal-Mart and Carrefour in the Korean retail market. For this discussion, this paper compared the marketing strategies of the big four retailers in Korea: Wal-Mart, Carrefour, E-mart, and Samsung- TESCO. E-mart is the Korean retailer which beat Wal-Mart and Carrefour and took the number one position in the Korean retail market with a unique marketing strategy. Samsung-TESCO is a multinational company showing successful localization in the Korean retail market. Through the comparison of the factors resulting in the success or failure of the above retailers, the four factors that have caused the withdrawal of Wal-Mart and Carrefour are presented as the following: ignorance of paradigm for the competition in Korean discount retailing, failure of localization, ineffective supply chain management, and low merits of the Korean market due to the emerging Chinese market. Many multinational companies have considered launching their business in the countries with a strange market environment, culture, and consumers. In particular, some Asian countries like Korea, Japan, and China have a very attractive retail market, but these markets are not familiar to them. Thus, this paper will show useful information on how a foreign retailer can successfully establish a foothold in those markets. Moreover, analyses in this paper can be used as a case study for future research.
Keywords: Korean retail market; multinational enterprises; localization; Korean retail market; multinational enterprises; localization